Crop wild relatives in Vologda Province - L. Yu. Shipilina (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Searching for new sources of genes for cultivated plants in order to increase their productivity, earliness, resistance, etc. is the vital problem of scientific work, since the need of mankind for food has increased in recent years many times. The development of biotechnological and molecular biological methods makes it possible to involve crop wild relatives (CWR) in breeding programs.Materials and methods. The material was the published reference data of the vegetation in the studied area and the expedition materials collected by VIR's staff and the author.Results and conclusion. A revision was made on crop wild relatives in the vegetation of Vologda Province: 260 species belonging to 106 genera and 22 families were identified. Floristic areas most important for further research were named: Mologo-Vologdsky, Verkhnesukhonsky, as the richest in CWR composition, which was caused by a combination of Boreal, Arctic and European species, and Yugsky Districts, where a large number of Ural-Siberian species of CWR occur. The northern districts have a poor diversity of species, but it is here that the most valuable cranberry swamps are located. Sheksninsko-Sudsky, Vozhega-Kubensky, Verkhnesukhonsky and Nizhnesukhonsky Districts with their 57 protected areas of different ranks conserve 29 species of CWR listed in the Red Book of Vologda Province.